Women Agency in Community-based Disaster Preparedness - Irfiade Zarkasyi Talaththof; Siti Zunariyah (Universitas Sebelas Maret (UNS), 2021)
The geographical condition of Indonesia is included in vulnerable areas where each region has diverse disaster risks. Various disasters often occur such as floods, landslides, earthquakes and so on. Therefore preparedness is needed before and after a disaster. To achieve preparedness we need access and control of resources. Women are often looked down upon by others and are seen as a weak group so that they are deemed not to have a strong ability to deal with various kinds of disaster conditions. The purpose of this research is to find out the women agency in community-based disaster preparedness. The root of this research theory uses Anthony Giddens's structuration theory which discusses the duality of agent and structure interactions. This research uses a qualitative research method with a descriptive approach. The informant selection technique in this study was purposive sampling which chose SIBAT women as key informants. The data used are primary and secondary data through interview, observation and documentation techniques. Test the validity of the data using source triangulation techniques. Data analysis in this study began with data collection, data reduction, data presentation, and continued with drawing conclusions.The ultimate goal is how to ensure women are resilient so they can coexist with disaster risk. Then the further question is how far the agency is, how vulnerable group is part of the effort to manage risk, or how they adapt to change and pressure. Although they depart from a strong informal community network (SIBAT) both in terms of information disclosure and the process of disaster management, it can be called a part of the structure that makes room for women's agency.The results showed that women have an agency that jumped from the general view that women have been perceived as a vulnerable group and are capable of having the capacity to deal with various vulnerabilities. SIBAT women are able to run agencies of Reproductive in the fields of ecology, economic, social, physical, and education. There are several factors that affect agents being able to jump into an agency when the actors make changes. The factors that influence women agency in terms of preparedness are opportunity and motivation, family support and family reason, and last but not least is participation and regeneration. Keywords : Women, Agency, Vulnerability, Capacity